Nanobodies effectively modulate the enzymatic activity of CD38 and allow specific imaging of CD38+ tumors in mouse models in vivo. Issue 1 (December 2017) - Fumey, William; Koenigsdorf, Julia; Kunick, Valentin; Menzel, Stephan; Schütze, Kerstin; Unger, Mandy; Schriewer, Levin; Haag, Friedrich; Adam, Gerhard; Oberle, Anna; Binder, Mascha; Fliegert, Ralf; et al.
Abstract The cell surface ecto-enzyme CD38 is a promising target antigen for the treatment of hematological malignancies, as illustrated by the recent approval of daratumumab for the treatment of multiple myeloma. Our aim was to evaluate the potential of CD38-specific nanobodies as novel diagnostics for hematological malignancies. We successfully identified 22 CD38-specific nanobody families using phage display technology from immunized llamas. Crossblockade analyses and in-tandem epitope binning revealed that the nanobodies recognize three different non-overlapping epitopes, with four nanobody families binding complementary to daratumumab. Three nanobody families inhibit the enzymatic activity of CD38in vitro, while two others were found to act as enhancers.In vivo, fluorochrome-conjugated CD38 nanobodies efficiently reach CD38 expressing tumors in a rodent model within 2 hours after intravenous injection, thereby allowing for convenient same dayin vivo tumor imaging. These nanobodies represent highly specific tools for modulating the enzymatic activity of CD38 and for diagnostic monitoring CD38-expressing tumors.